The Meaning of Amânâh In Managing Household Finances Towards Blessing - Luluk Latifah; Abd Hadi; Sholihul Huda; Abdurrahman Raden Aji Haqqi; Lutfi Agus Salim (Universitas Darussalam Gontor, 2024)
Amānāh is all religious obligations or burdens covering the affairs of the world and the hereafter which are addressed to humans. The concept of Amānāh that is built cannot be separated from the cultural and social influences of one’s place of residence. This study aims to develop the concept of Amānāh values from household financial managers and scientific experts by using a phenomenological qualitative approach from the main informants as housewives and from experts in various scientific fields, namely the field of Islamic economics, Islamic religion, psychology and sociology. The results of the research show that the concept of the meaning of Amānāh is a mandate, an honesty, a trust and proportionality.